TEKNIK PEMBUATAN PERNIS DARI DAMAR UNTUK USAHA KECIL - E Edriana; Erik Dahlian; E Suwardi Sumadiwangsa (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
This study was intended to identify an appropriate formula ill manufacturing varnish for a small-scale industry. Resin used in the formula consisted of two types, namely